Corrosion Resistance of Hsla Steel after Various Surface Treatments in Chloride Environment - Kamil Borko; Filip Pastorek; Stanislava Fintova; Branislav Hadzima (Communications, 2016)
The effect of mechanical and chemical surface treatment of high-strength low alloy steel S355J2 on its electrochemical characteristics was investigated by voltamperic tests in corrosive environment of 0.1M NaCl solution simulating sea atmosphere. Mechanical surface treatment was done by grinding on 1200 grit paper and by sandblasting. Chemical surface treatment was performed by iron phosphating in aqueous solution of H3PO4 and FeCl3.6H2O. Thermodynamic and kinetic corrosion characteristics including corrosion potentials and corrosion current densities were measured and analysed by potentiodynamic polarisation curves and Tafel analyses respectively. The positive combination of these two techniques on corrosion properties of S355J2 steel surface was reported.